2010
DOI: 10.1007/s11695-010-0171-6
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Gene Networks in Morbidly Obese Patients With Nonalcoholic Fatty Liver Disease

Abstract: This study reveals the canonical pathways and gene networks associated with NAFLD in morbidly obese Caucasians. The application of gene network analysis highlights the transcriptional relationships among NAFLD-associated genes and allows identification of hub genes that may represent high-priority candidates for NAFLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 82 publications
(85 reference statements)
1
28
0
Order By: Relevance
“…A recent study analyzed hepatic gene networks in morbidly obese patients with NAFLD (BMI 49.6 ± 7.4 kg/m 2 , n = 24, 89% female) or without NAFLD (BMI 48.8 ± 5.9, kg/m 2 , n = 25, 96% female) (31). Three genes associated with the fibrosis pathway (COL1A1, IL10, and IGFBP3) were upregulated and one gene associated with the UPR (HSPA5, also known as GRP78) was downregulated in patients with NAFLD compared with patients without NAFLD.…”
Section: Activation Of the Upr In Human Obesity And Nafldmentioning
confidence: 99%
“…A recent study analyzed hepatic gene networks in morbidly obese patients with NAFLD (BMI 49.6 ± 7.4 kg/m 2 , n = 24, 89% female) or without NAFLD (BMI 48.8 ± 5.9, kg/m 2 , n = 25, 96% female) (31). Three genes associated with the fibrosis pathway (COL1A1, IL10, and IGFBP3) were upregulated and one gene associated with the UPR (HSPA5, also known as GRP78) was downregulated in patients with NAFLD compared with patients without NAFLD.…”
Section: Activation Of the Upr In Human Obesity And Nafldmentioning
confidence: 99%
“…Further, it may be advantageous to put focus on canonical pathways and networks instead of single genes when the aim is to obtain insight in the pathophysiology of complex diseases, such as preeclampsia. The high interconnectivity of focus genes with other correlated genes within a biological network may imply functional and biological importance of these genes 26, 27. To be able to assess this in a comprehensive manner, we increased the FDR cut off to 0.1 and consequently the number of genes included in the analysis.…”
Section: Commentmentioning
confidence: 99%
“…Persistent activation of the UPR, on the other hand, is associated with the pathogenesis of a number of metabolic diseases [1, 2]. Chronic UPR activation has been observed in liver and/or adipose tissue of dietary and genetic murine models of obesity, and in human obesity and non-alcoholic fatty liver disease (NAFLD) [39]. Activation of the UPR typically occurs in response to the accumulation of unfolded proteins in the ER lumen, termed ER stress, however recent studies have demonstrated that ER membrane events independent of the ER lumen can trigger the UPR.…”
Section: Introductionmentioning
confidence: 99%